Case report: Complete resection of invasive thymoma invading the superior vena cava and right atrium under cardiopulmonary bypass support - Zhang, Xiangxin; Chen, Liang; Zhou, Wenyong; Wang, Zhexin; Wang, Chong; Shi, Jianxin; Yao, Feng (Frontiers in Oncology, 2022)
Here we describe an uncommon case of a 48-year-old male patient with an invasive thymoma invading the superior vena cava, bilateral innominate veins, right internal jugular vein, right subclavian vein, right atrium, azygos vein, and part of the lung tissues. The tumor was resected entirely under cardiopulmonary bypass support, and the venous bypass using a vascular graft was successfully established between the left innominate vein and the right atrium. The postoperative course was uneventful, and the patient was discharged 15 days after surgery without complications.